Has Indonesia’s Unique Progressivism in Mandating Corporate Social Responsibility Achieved Its Ends? - Soonpeel Edgar Chang (Sriwijaya Law Review, 2018)
It has been a decade since Indonesia implemented its first mandatory CSR requirement. The time is ripe for the discussion: can Indonesia confidently say that it has saved Indonesia by making companies publicly answer for many social issues? Can it successfully bring social and economic justice by continuously enforcing this radical progressivism or utilitarianism? To begin to address these questions, this paper first examines Indonesia's unique features that strengthen CSR as a legal obligation and analyzes the current regulatory frame of CSR. Then, it discusses whether these laws and regulations have actually worked as a practical tool to encourage and enforce companies to perform CSR activities. This research concludes that company law can save Indonesia despite its failure so far due to a number of problems in and out of positive law. It suggests how it can specifically structure the CSR regulations and seeks attention to the more structural reform from the longer-term goal of developing a national mechanism.